Probing the CP nature of the top-Higgs Yukawa coupling in tt[bar]H and t H events with H → bb[bar] decays using the ATLAS detector at the LHC - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; et al. (Physics letters, 2024)
The CP properties of the coupling between the Higgs boson and the top quark are investigated using 139 fb−1 of proton-proton collision data recorded by the ATLAS experiment at the LHC at a centre-of-mass energy of s=13 TeV. The CP structure of the top quark-Higgs boson Yukawa coupling is probed in events with a Higgs boson decaying into a pair of b-quarks and produced in association with either a pair of top quarks, tt¯H, or a single top quark, tH. Events containing one or two electrons or muons are used for the measurement. Multivariate techniques are used to select regions enriched in tt¯H and tH events, where dedicated CP-sensitive observables are exploited. In an extension of the Standard Model (SM) with a CP-odd admixture in the top-Higgs Yukawa coupling, the mixing angle between CP-even and CP-odd couplings is measured to be α=11−73∘∘+52∘, compatible with the SM prediction corresponding to α=0.